A Study on Anterior Longitudinal Ligament Ossification in Vertebral Spine Patient (Medical Forum Monthly, 2023)
Objective: The basic aim of the research is to perform a study on anterior longitudinal ligament ossification in vertebral spine patient.Study Design: Cohort study retrospective studyPlace and Duration of Study: This study was conducted at the Women Medical College Abbottabad and Ayub Medical College Abbottabad from January 2023 to June 2023.Materials and Methods: Patient records were retrieved from the medical records departments of the respective medical colleges.Results: A total of 150 patient records were reviewed during the study period from January 2023 to June 2023. The study cohort consisted of 53 males (53%) and 47 females (47%), with ages ranging from 25 to 75 years and a mean age of 52 years. The distribution of patients among different age groups showed a relatively even representation across the decades. Common clinical symptoms reported by the patients included localized pain (78%), stiffness (64%), and radiating pain (42%) along the affected spinal segments.Conclusion: It is concluded that this study enhances our understanding of ALL ossification, its clinical implications, and treatment outcomes. By recognizing the complex nature of this condition, healthcare practitioners can optimize patient care and contribute to the ongoing advancements in diagnosis and treatment strategies.